An ecological study of the fern Asplenium Trichomanes L. in Iraq with a reference to its phytochemical and antioxidant activity. Issue 1 (June 2021) - Ismail, A M; Hamdi, B A; Maulood, B K; AL-Khasreji, T.O.
Abstract: A number of ferns are known to have ornamental, medicinal and ethnobotanical importance all over the world. In spite of the presence of numerous fern species such as Equisetum, Adiantum, Asplenium and Cheilanthes species all over our country (Iraq) particularly the Kurdistan part, still, such information in this area is quite rare. Asplenium Trichomonas L. is a genus of one of the widest groups of Asplenideae (maidenhair spleen worts). It is a megaphyllous, homosporous fern, which was found at an elevation above 1600 m.a.s.l. Samples were collected from the Taweela area in Kurdistan of Iraq, the phytochemical and antioxidant activity of the plant was dealt with in the current investigation through the methanol extract method of ferns. The result revealed positive detection of few numbers of flavonoid compounds, among which kaempferol compound showed the highest concentration (227 μg/ml) whereas kaempferide 3-0 glycoside showed the lowest concentration (130.3 μg/ ml), six phenolic compounds were identified through HPLC technique among which (Kaempferol, Quercetin, Myrstin, Rutin, Kea.3-o-glycoside, and Leutolin), also anti-oxidant activity recorded (1c50) it had exceeded (2.27 μg/m1). In contrast the positive control (Ascorbic acid) 0.018 mg/ ml. The present study has been devoted to the distribution of Asplenium Trichomanes L in Iraq with reference to it is a phytochemical and anti-oxidant activity for the first time in the region. In years to come, undoubtedly this will follow with more investigations on fern wealth in Iraq so it will reduce the existing gap in the knowledge in this respect.